UJI AKTIVITAS KITINASE ISOLAT - ISOLAT BAKTERI YANG DIISOLASI DARI PETIS UDANG - , ENY ORINDA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objectives of this research was to determine the growth curve, production of extracellular protein and chitinase activities of five chitinolytic bacterial isolates